Assessment of nutritional behaviours of children aged 7-12 attending to primary schools in Biala Podlaska, Poland - Anna Galczak-Kondraciuk; Paweł Stempel; Jan Czeczelewski (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. Children and youth constitute a group that is particularly prone to the effects of improper diet. In the puberty period, numerous significant lifestyle choices are made, for instance regarding particular nutritional behaviours which may be repeated later in life and may determine the state of health. Objective. The aim of the study was to assess nutritional behaviours of children aged 7-12 attending to primary schools in Biala Podlaska county (Eastern Region of Poland). Material and methods. The study included 1643 children aged 7-12 from primary schools in Biala Podlaska county. The research was carried out in 2015. The questions included in the questionnaire prepared by the authors regarded the number and regularity of meals, the types of products (mainly fruit and vegetables, sweets, fizzy drinks, fast food, milk and dairy products) and the frequency of consuming them during these meals and between them. Differences between the responses to the questions in groups divided according to gender were analysed with the use of χ2 test (G function). Results. It was revealed that 672 girls (81.7%) and 633 boys (71.9%) had at least four meals a day, while as many as 23% of the girls and boys did not have breakfast before going to school and 33.5% of the girls and 37.4% of the boys did not take lunch to school. The main meal (dinner) was eaten every day by 652 girls (78.5%) and 605 boys (74.5%). Products most commonly eaten between the main meals were fruit and vegetables (51% of the girls and 42.4% of the boys), while sweets were consumed 2-3 times a week by 37.2% of the girls and 36.1% of the boys. The consumption of dairy products (milk, natural yoghurt and/or kefir) once a week or less frequently was declared by 53% of the girls and boys. Conclusions. Assessment of nutritional behaviours revealed numerous mistakes which may negatively affect the development of the study participants. In the light of the above findings, it seems necessary to provide children and their parents with nutritional education in order to develop proper nutritional behaviours and correct the mistakes.